East Asia Update, October 2001 : Regional Overview - World Bank (World Bank, Washington, DC, 2020)
Governments' first instincts are often to attempt to tackle weaknesses in public financial accountability by investing in computerization of financial management information systems. However, in most East Asian contexts the World Bank advises countries that reforms need to start not from the technical hardware of IT but from an effectively implemented reform of the foundations of public financial accountability, starting with budget management processes and the control regime. Immediate priority steps include: reforming the budget process to improve policy prioritization and fiscal discipline, including integration of off-budget accounts into the main budget; better coordination of planning and budgeting; better coordination of current and capital expenditure; more rigorous medium-term fiscal and expenditure planning; greater ownership of budgets by line departments and frontline service providers; the integration of performance information into the budget formulation process; and streamlining both internal and external management control systems. Countries such as Thailand, Vietnam, Indonesia and the Philippines are working with the World Bank to modernize public financial accountability institutions.